Identification and measurement of dystonia in cerebral palsy. (8th August 2017) - Rice, James; Skuza, Pawel; Baker, Felicity; Russo, Remo; Fehlings, Darcy
Abstract : Aim: To establish the prevalence and severity of dystonia in a population of children with cerebral palsy (CP) with hypertonia assessment and measurement tools. Method: A cross‐sectional study of 151 children (84 males, 67 females) with CP who were assessed with the Hypertonia Assessment Tool (HAT) and Barry‐Albright Dystonia scale (BAD) for identification and measurement of severity of dystonia. HAT dystonia items were assessed for construct and convergent validity. Results: Distribution by predominant motor type (PMT) was: 85% spastic, 14% dyskinetic, and 1% ataxic. Spastic and dyskinetic groups showed widespread evidence of dystonia according to HAT profiles and BAD scores. The dyskinetic PMT group had a higher mean BAD score than the spastic group (difference of 13 units, 95% CI 9.1–16.4). Dystonia severity (BAD score) increased linearly across gross motor ( p <0.001), manual ability ( p <0.001) and communication functional levels ( p <0.001). Divergence was noted in how HAT item six identified dystonia compared to items one and two. Interpretation: The HAT provided an estimate of the prevalence of both spasticity and dystonia in a large CP population, beyond predominant motor type. Dystonia is a common finding in the spastic PMT group, and its severity increases as motor function worsens. What this paper adds: Dystonia is readily identified in cerebral palsy (CP) using the Hypertonia Assessment Tool, regardless of the predominant motor type. Spasticity and dystonia frequently coexist in the CP population. Severity of dystonia is inversely related to motor function. What this paper adds: Dystonia is readily identified in cerebral palsy (CP) using the Hypertonia Assessment Tool, regardless of the predominant motor type. Spasticity and dystonia frequently coexist in the CP population. Severity of dystonia is inversely related to motor function. This article is commented on by Supiot on page1211 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.